2012
DOI: 10.1542/peds.2011-2347
|View full text |Cite
|
Sign up to set email alerts
|

Triage Nurse Initiation of Corticosteroids in Pediatric Asthma Is Associated With Improved Emergency Department Efficiency

Abstract: Triage nurse initiation of oral corticosteroid before physician assessment was associated with reduced times to clinical improvement and discharge, and reduced admission rates in children presenting with moderate to severe acute asthma exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 26 publications
2
67
0
5
Order By: Relevance
“…This finding suggests that the rate of exposure to triggers, experiencing disease symptoms, and using medications for these reasons decreased because of the asthma management program used in this study. Other studies also indicated that bronchodilators and corticosteroids are frequently used [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the rate of exposure to triggers, experiencing disease symptoms, and using medications for these reasons decreased because of the asthma management program used in this study. Other studies also indicated that bronchodilators and corticosteroids are frequently used [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…[712] In the original randomized controlled trials of efficacy, corticosteroids were administered within one hour of ED arrival. [6, 7] Several recent studies have confirmed that timely corticosteroid administration is associated with reduced odds of admission [1315] and that every 30-minute delay in corticosteroid administration is associated with a nearly 20% increased odds of admission. [14] Consequently, the proportion of children receiving timely corticosteroids is a measure of ED quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…[11, 17, 1923] In addition, frequent delays in corticosteroid administration (52–78% of visits) have been reported. [1315, 21, 22] Studies from Canada, United Kingdom, South America, and Australia have demonstrated the value of ED clinical pathways in the management of pediatric asthma exacerbations. Pathways have been associated with increased frequency of appropriate corticosteroid administration, [15, 24] expedited corticosteroid administration, [13, 15] and decreased hospitalization rates, [13, 15, 25] ED LOS, [13, 26] prescribing errors [24] and return visits.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol was based on the 2007 NIH guidelines and designed to be nurseinitiated, as triage nurse-driven protocols have been shown to reduce hospital admissions, time to corticosteroid administration, time to patient improvement, and time spent by patients in the emergency department. [4][5][6] The effect of a nurse-driven protocol in the emergency department setting on patients with status asthmaticus has not been studied. The objective of this study was to examine the effects on time to initial treatment and adherence to evidencebased practice for status asthmaticus after the implementation of an evidence-based, nurse-initiated pediatric asthma protocol in our pediatric emergency department.…”
Section: Introductionmentioning
confidence: 99%